2009
DOI: 10.1007/s11033-009-9533-3
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum interleukin 17 in patients with systemic lupus erythematosus

Abstract: Interleukin 17 (IL-17) is a Th17 cytokine associated with inflammation, autoimmunity and defense against some bacteria, it has been implicated in many chronic autoimmune diseases including psoriasis, multiple sclerosis and systemic sclerosis. However, whether IL-17 plays a role in the pathogenesis of systemic lupus erythematosus (SLE) remains unclear. In the present study, we aimed to investigate the serum IL-17 level in patients with SLE and it's associations with disease manifestations and activity. Fifty-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
78
5
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(102 citation statements)
references
References 19 publications
17
78
5
2
Order By: Relevance
“…[15][16][17][18][19] Consistent with data from other labs, we report here that SLE patients have increased serum TNF-a levels. [43][44][45] TNF-a, a common marker for the activation status of macrophages and DCs, is primarily secreted by activated monocytes/macrophages and may induce the increased expression of Tim-4, thus promoting Th2 cell proliferation via interaction with Tim-1.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[15][16][17][18][19] Consistent with data from other labs, we report here that SLE patients have increased serum TNF-a levels. [43][44][45] TNF-a, a common marker for the activation status of macrophages and DCs, is primarily secreted by activated monocytes/macrophages and may induce the increased expression of Tim-4, thus promoting Th2 cell proliferation via interaction with Tim-1.…”
Section: Discussionsupporting
confidence: 87%
“…[12][13][14] Increased levels of inflammatory factors, such as IL-17 and tumor necrosis factor (TNF)-a, are detected in the serum from patients with SLE. [15][16][17][18][19] Macrophages, a major cellular constituent of innate immunity and an effective antigen presenting cell (APC) for bridging innate and adaptive immunity, have been widely linked to lupus development. Existing studies focus mainly on defects in macrophage or dendritic cell (DC) phagocytosis, resulting in accumulation of apoptotic debris leading to an array of autoimmune phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…However, in some reports, no association of IL-17 with clinical markers of disease activity was found [22,23]. These inconsistencies are partly due to enrolment of patients regardless of the immunosuppressive therapy or at a different phase of their disease.…”
Section: Discussionmentioning
confidence: 98%
“…In patients with active SLE, both the increase in percentage of circulating Th17 cells, [12,18,19] and elevated serum concentration of IL-17A have been described [20][21][22][23][24]. However, in some reports, no association of IL-17 with clinical markers of disease activity was found [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…To reach a definitive conclusion, further studies based on better design are needed. In spite of these, many previous studies have revealed that IL-17, the signature cytokine of the newly described T helper 17 (Th17) cell population, was implicated in the pathogenesis of numerous autoimmune diseases including RA [2][3][4][5][6]. Hopefully, IL-17 may prove to be a promising therapeutic target in RA.…”
mentioning
confidence: 99%